Industrial quality control study on La Croesus Pharma, Inc. - Buenviaje, Arlene C. (College of Engineering, 2003)
The study conducted on La Croesus Pharmaceutical, Inc. deals with the company's concerns with their 500 milligram Amoxicillin capsule product. This particular product was chosen because it makes up the largest portion of the company's sales accounting for around 30 percent of the sales volume. The group aims to analyze and generate recommendations on the factors affecting the rejection rate of the Amoxicillin capsules. Based on the constructed Pareto chart, the top three concerns that contribute the most to rejection were found to be physical defects, fill weight, and potency. The group subsequently focused on these three main problems for the study. The first problem concerning physical defects is considered to be an attribute problem. Statistical process control analysis was conducted by constructing the p-chart for the data on physical defects collected from September 2000 until October 2001. Based on the p-chart, the process was found to be out of control. To address this matter, the team recommends that machine settings be standardized and recorded, after which a design of experiments must be conducted to find out the optimal machine settings to lessen physical defects. Furthermore, the team also recommends a temperature monitoring system to avoid the unnecessary exposure of the Amoxicillin capsules to high temperatures, which make the capsules conducive to physical defects. Finally, it was concluded that La Croesus Pharmaceutical, Inc. adopt the use of the p-chart to further monitor process variability. The second problem addressed in the study, nonconformance to fill weight specifications, is a variable problem. Again, statistical process control analysis was conducted. Three sets of X-bar and S charts were constructed for the months of August, September and October of 2001. Based on the control charts, the process was found to be out of control. It was also found to be off-target with an estimated probability of nonconformance of 96.78 percent. Based on the capability analysis, the process capability index is determined to be 0.617 which means that the process is performing with inadequate capability. To help remedy this problem, the group recommended ways to determine the speed settings being used in the encapsulating machine. It is also recommended that X-bar and S charts be used by La Croesus Pharmaceutical, Inc. to monitor variability in the encapsulating process. The last problem addressed in the study is also another variable problem, nonconformance to percent potency. Statistical process control analysis was done also by constructing X-bar and S charts for August, September, and October 2001. Percent nonconforming was estimated to be about 0.97 percent. Based on the control charts, the process was found to be out of control. Based on the capability analysis, the process was found to be operating at marginal capability with a capability index of 1.082. Recommendations were generated to address this in terms of effectively monitoring the temperature and relative humidity of the processing and storage rooms. Statistical process control must also be done by the company for percent potency (constructing and analyzing X-bar and S charts in particular).